The engineer’s Instruction for rectification of opening for escalator in grid ‘X, 19-20 & W, 19-20’ of B1 to B1 (A-) - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the engineer’s Instruction for rectification of opening for escalator in grid ‘X, 19-20 & W, 19-20’ of B1 to B1 (A- of BRACU new campus project site.